Impact of different schemes for treating landfill leachate. (January 2018) - Di Maria, Francesco; Sisani, Federico; Contini, Stefano; Ghosh, Sadhan K.
Highlights: Different treatment schemes for the leachate based on evaporation, RO and WWTP were analysed by LCA. New inventories were built based on experimental data. Midpoint HTc, HTnc and FWeco were higher for WWTP and evaporation. Endpoint EQ (PDF ∗ m 2 /year) was higher for RO. Abstract: Different technological schemes for treating the leachate generated by an existing landfill were compared in a life cycle perspective. On-site advanced processes based on reverse osmosis and evaporation were compared to conventional off-site co-treatment with civil sewage in wastewater treatment plant (WWTP). The inventories of the different scenarios were built by both direct observation of existing facilities and by retrieving data from the literature and similar equipment. Particular care was given for evaluating the energetic and chemical needs for operating the on-site advanced treatments. The evaporation system required 40 kW h/m 3 of electricity and 18.5 kW h/m 3 of heat, whereas reverse osmosis needed only 8.5 kW h/m 3 of electricity. On the other hand the amount of liquid concentrate returned by the evaporation system was only about 0.03 m 3 /m 3 instead of about 0.30 m 3 /m 3 returned by reverse osmosis. The evaporation system also consumed the highest amount of chemicals. Life cycle analysis showed that the impact categories most affected by the different options were human toxicity, both non-cancer and cancer, together with freshwater ecotoxicity. The uncertainty analysis highlighted the major contribution associated with direct emissions from the processes. On the basis of mean values, the qualitative trends were substantially confirmed.